Individualised nursing care in cancer care - Charalambous, Andreas (My University, 2018)
© Springer International Publishing AG, part of Springer Nature 2019. An ideal patient-centred care (or individualised care) environment is necessary within the cancer care context and across the cancer continuum. Persons diagnosed with and living with cancer are facing many varying challenges that can threaten their human dimensions in their totality. Cancer as a disease is typified by emotional, social, spiritual and physical challenges that can be strengthened further by complex treatments, treatment-induced toxicities and uncertain outcomes. These overall effects of cancer and its treatments can negatively influence the perceived quality of nursing care, the patient’s quality of life (health status) and trust towards the healthcare professionals. The impact of cancer on the person can be significant but can never be uniformly across different persons. As each person is unique, it is expected that cancer’s touch will differ in terms of how the patient is affected and to what extent. By definition this will result in triggering different needs and expectations for the persons affected by cancer. The aim of this chapter is to introduce the reader to the unique conditions induced by cancer and its treatment within the cancer context with reference to the individuality of the person. The way that individualised care can mitigate the impact of cancer on the person by placing the person at the centre of the care will be presented. Finally, the associations between concepts such as quality of oncology care and perceived quality of life with individuality will be lay down to emphasise on the complexity of cancer’s impact on the person.
Keywords: Cancer context; Care; Communication; Individualised care; Model